Mycoremediation Potential of Synthetic Textile Dyes by Aspergillus niger via Biosorption and Enzymatic Degradation: 10.32526/ennrj/20/202100171 - Ekanayake, Manavi Sulakkana; Manage, Pathmalal (Environment and Natural Resources Journal, 2022)
Textile dyes that persist in the environment are highly resistant to the natural degradation processes that occur in the environment. Therefore, the present study isolated, identified, and optimized textile dye decolorization by fungi and elucidated the dye decolorization pathway to develop a low-cost biotechnological approach for decolorization and detoxification of textile dyes. Within 36 hours of incubation at temperatures ranging from 28 to 40°C, pH 7, and shaking at 100 rpm, Aspergillus niger MN990895, which was selected from a total of 77 fungal isolates, completely decolorized the model dye CI Direct Blue 201 (DB 201). A. niger biosorbed 8.4±1.2% of the dye used where live biomass showed complete dye removal. It was found that extracellular crude enzymes were more involved in DB 201 dye decolorization (72.7±3.3%) than intracellular crude enzymes. The enzymatic studies suggested that the primary enzyme involved in DB 201 textile dye decolorization was lacccase, which was further confirmed by the presence of distinct protein bands around 75-100 kDa on the SDS-PAGE. The FTIR spectra and seed germination assays confirmed that A. niger proved successful in DB 201 textile dye degradation and detoxification. The present study suggests that A. niger may have promising implications in the future for the development of an enzyme-based textile wastewater treatment system.